Escherichia coli O80 hybrid pathotype strains producing Shiga toxin and ESBL: molecular characterization and potential therapeutic options. (26th November 2019) - Cointe, Aurélie; Birgy, André; Bridier-Nahmias, Antoine; Mariani-Kurkdjian, Patricia; Walewski, Violaine; Lévy, Corinne; Cohen, Robert; Fach, Patrick; Delannoy, Sabine; Bidet, Philippe; Bonacorsi, Stéphane
Abstract: Objectives: Enterohaemorrhagic Escherichia coli (EHEC) infections may be complicated by haemolytic uraemic syndrome (HUS). The emerging worldwide EHEC serogroup O80 has acquired a mosaic plasmid combining extraintestinal virulence and antibiotic resistance. This hybrid pathotype is associated with invasive infections that require antibiotic therapy, classically not recommended in EHEC infections, increasing the risk of HUS. We characterized two ESBL-producing O80 EHEC strains, which is an unusual resistance mechanism among EHECs, and determined the safest therapy to be used for invasive infections. Methods: WGS of two strains isolated from the stools of an asymptomatic carrier and a patient with HUS was performed using Illumina and Nanopore technologies. Generated reads were combined to assemble genomes. We determined the safest therapy by comparing Shiga toxin (Stx) production by the two strains in the presence of several antibiotics. Results: The strains were genetically close to the O80 EHEC clone, belonging to ST301 and harbouring stx2d, eae -ξ, ehxA and genes characteristic of the extraintestinal virulence plasmid pS88. Long-read sequencing identified the acquisition of an additional plasmid harbouring CTX-M-type genes ( bla CTX-M-14 and bla CTX-M-1 ). Azithromycin decreased Stx production at subinhibitory concentrations, ciprofloxacin increased it and imipenem had no major effect. The combination of azithromycin and imipenem overall reduced Stx production. Conclusions: Acquisition of an additional plasmid harbouring ESBL genes is a step towards increasing the risk of O80 EHEC dissemination and represents a serious public health concern. The combination of azithromycin and imipenem reduced Stx production and suggests that this combination could be tested in clinical trials.